KORELASI IPK SARJANA DAN TRY OUT AIPKI DENGAN NILAI COMPUTER-BASED TEST UJI KOMPETENSI MAHASISWA PROGRAM PROFESI DOKTER PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS LAMPUNG - Chalida, Aprilly Adlina; Oktafany, Oktafany; Oktadoni Saputra; Nabilla, Nabilla (Nusantara Hasana Journal, 2025)
The Medical Professional Competency Examination (UKMPPD) is a national assessment designed to ensure the quality and competence of medical graduates in Indonesia. The high proportion of retakers in the Computer-Based Test (CBT) UKMPPD at several institutions, including the Faculty of Medicine, University of Lampung, highlights the need to identify academic factors associated with examination success, such as undergraduate Grade Point Average (GPA) and AIPKI Try-Out scores. This study aimed to analyze the correlation between undergraduate GPA and AIPKI Try-Out scores with CBT UKMPPD results among medical professional program students at the Faculty of Medicine, University of Lampung, during the February 2024–August 2025 period. This study employed a descriptive-analytic design with a cross-sectional approach. Secondary data were obtained from the academic office of the Faculty of Medicine, University of Lampung. A total of 361 students who met the inclusion and exclusion criteria were included in the analysis. Data were analyzed using descriptive and bivariate methods with correlation tests. The results showed that the mean undergraduate GPA was 3.26, the mean AIPKI Try-Out score was 56.77, and the mean CBT UKMPPD score was 78.77. Statistical analysis demonstrated a strong positive correlation between undergraduate GPA and CBT UKMPPD scores (r = 0.637; p = 0.001), as well as between AIPKI Try-Out scores and CBT UKMPPD scores (r = 0.741; p = 0.001).